Jazz. Episode eight, Risk [videorecording (DVD)] - Burns, Ken, 1953- (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
Between 1945 and 1955, jazz splinters into different camps: cool and hot, East and West, traditional and modern. One by one, the big bands leave the road, but Duke Ellington keeps his band together, while Louis Armstrong puts together a small group, the "All-Stars." Promoter Norman Granz insists on equal treatment for every member of his integrated troupes on his Jazz at the Philharmonic Tours. Meanwhile, bebop musicians Dizzy Gillespie and Charlie Parker are creating some of the most inventive jazz ever played but a devastating narcotics plague sweeps through the jazz community, ruining lives and changing the dynamics of performance. And a number of great performers, including Miles Davis, Dave Brubeck, Gerry Mulligan, Thelonious Monk, Paul Desmond, Bille Holiday, Ella Fitzgerald, and John Lewis, find new ways to bring new audiences to jazz.